Für Kunst und Freundschaft das Borgo Ensemble - Dippel, Andrea 1969-; Bergmann, Reiner 1950-; Egersdörfer, Matthias 1969-; Frambach, Ludwig 1954-; Hanisch, Max 1991-; Wild, Marian 1982- (Verlag für moderne Kunst, 2023)
"For art and friendship" is the motto of the artist collective Borgo Ensemble. In 2009 originally founded as a music group by the object and performance artist Reiner Bergmann, developed in the following years a busy artist groups in Nürenberg. The ensemble showed its potential so far at different locations, including a administration house, Residential buildings and a car dealership, each of this location not only serves as a meeting place, but also as Exhibition and event locations. Basis for the creative collaboration of the registered association Borgo Ensemble, which operates in a former post office, is an expanded artistic term: in addition to painting, drawing, sculpture and installation, also music, performance, philosophical Lectures and the legendary Cinema borgese – a series of short films. This Book not only presents the previous locations, but also 32 main protagonists with their works. Texts by Reiner Bergmann, Andrea Dippel, Matthias Egersdörfer, Ludwig Frambach, Max Hanisch and Marian Wild lead the way through history and the present of the Borgo Ensemble
Impressum: Diese Publikation erscheint als Band 15 der Schriftenreihe der Kunstvilla im KunstKulturQuartier anlässlich der Ausstellung "Für Kunst und Freundschaft - Das Borgo Ensemble" vom 25. November 2023 bis 5. Mai 2024
Keywords: Borgo Ensemble; Geschichte 2009-2023; Geschichte; Künste; Künstlervereinigung; Musik; Kunst; Nürnberg; Kunstvilla; Kulturquartier; Ausstellungskatalog -- Kunstvilla im KunstKulturQuartier -- 25.11.2023-05.05.2024 -- Nürnberg; Ausstellungskatalog -- Kunstvilla KunstKulturQartier -- 25.11.2023-05.05.2024 -- Nürnberg